Pandemia global y desigualdades locales: implosión política, económica y social en México - Jaime Aragón Falomir (Études Caribéennes)
The objective of this article is to analyze and determine the consequences of the health pandemic in the context of worsening inequalities. For this research, we follow the literature on inequalities, mobility, elites and democracy that has identified the consequences of COVID-19 in political, economic and social life in Mexico. By intertwining these three variables, we show how a sanitary crisis is revealing, amplifying, making visible and creating new inequalities. We also show that the burdens with which Mexico arrives will be aggravated by the pandemic. We note that the elites should play a more central role in contributing to the reduction of socio-economic gaps and, above all, understand that perception is not always reality. Then, we note that pandemic working conditions have already revealed new inequalities by exemplifying it with data showing that remote work is a privilege of minorities. This paper contributes to the state of the literature on COVID-19, Mexico and inequalities by seeking to understand how a pandemic heterogeneously affects the world, its societies and especially the different socio-economic strata.